2004
DOI: 10.1016/j.ssc.2004.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Correlated vortex pinning in Si-nanoparticle doped MgB2

Abstract: The magnetoresistivity and critical current density of well characterized Si-nanoparticle doped and undoped Cu-sheathed MgB2 tapes have been measured at temperatures T ≥ 28 K in magnetic fields B ≤ 0.9 T. The irreversibility line Birr(T ) for doped tape shows a stepwise variation with a kink around 0.3 T. Such Birr(T ) variation is typical for high-temperature superconductors with columnar defects (a kink occurs near the matching field B φ ) and is very different from a smooth Birr(T ) variation in undoped MgB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…For this sample set the best results (10 5 A cm −2 and 10 4 A cm −2 at 6 T and 11.5 T, respectively) are found when the excess-Mg level is raised to 15% and SiC is added. Still further improvements are depicted in figure 7 which emphasizes the effectiveness of [49] Nanodiamond [57][58][59] HoO 2 [70] Zr [77] Malic acid [87] ZrB 2 [5,44] TiC [60,61] A l 2 O 3 [71] Mo [78] Maleic anhydride [41] TiB 2 [5] S i C [ 38,42,[62][63][64][65] MgO [45] F e [ 79] Paraffin [88] NbB 2 [5] B 4 C [40, 66, 67] T i O 2 [72] C o [ 80] Toluene [89] Na 2 CO 3 [68] P r 6 O 11 [73] Ni [80] Ethanol [89] CaB 6 [50] S i O 2 [74] C u [ 81] Acetone [89] WSi 2 [51][52][53] A g [ 82] Tartaric acid [90] ZrSi 2 [51,52] A l [ 83] Ethyltoluene [91] Si [84] La [85] the C-containing dopants e.g. maleic anhydride, SiC, and C itself when appropriately introduced.…”
Section: Critical Current Density and Its Enhancement By Doping And F...mentioning
confidence: 99%
“…For this sample set the best results (10 5 A cm −2 and 10 4 A cm −2 at 6 T and 11.5 T, respectively) are found when the excess-Mg level is raised to 15% and SiC is added. Still further improvements are depicted in figure 7 which emphasizes the effectiveness of [49] Nanodiamond [57][58][59] HoO 2 [70] Zr [77] Malic acid [87] ZrB 2 [5,44] TiC [60,61] A l 2 O 3 [71] Mo [78] Maleic anhydride [41] TiB 2 [5] S i C [ 38,42,[62][63][64][65] MgO [45] F e [ 79] Paraffin [88] NbB 2 [5] B 4 C [40, 66, 67] T i O 2 [72] C o [ 80] Toluene [89] Na 2 CO 3 [68] P r 6 O 11 [73] Ni [80] Ethanol [89] CaB 6 [50] S i O 2 [74] C u [ 81] Acetone [89] WSi 2 [51][52][53] A g [ 82] Tartaric acid [90] ZrSi 2 [51,52] A l [ 83] Ethyltoluene [91] Si [84] La [85] the C-containing dopants e.g. maleic anhydride, SiC, and C itself when appropriately introduced.…”
Section: Critical Current Density and Its Enhancement By Doping And F...mentioning
confidence: 99%
“…If intragranular pinning were dominant, then GB could simply provide transparency to the current, although in reality to some degree grain boundaries will always act to reduce J c . In fact, several studies [10,[13][14][15][16] have shown that small grain samples yield high J c and so the importance of GB pinning in MgB 2 appears to be unquestionable.…”
Section: Introduction: Pinning Mechanisms In Mgbmentioning
confidence: 99%
“…The disadvantage of pure MgB 2 is its quite low upper critical field B c2 (4.2 K) ∼ 18 T and weak flux pinning (which results in a low irreversibility field B irr (4.2 K) ∼ 12 T, and thus low critical current density in high fields). Flux pinning in pure MgB 2 is weak in spite of the same main pinning mechanism as in Nb 3 Sn [3] (grain boundary pinning [4,5]) due to rather clean boundaries and fairly large grains in normally prepared samples [4]. Further, in situ prepared MgB 2 samples [6] are very porous, which limits the magnitude of J c [7] and causes inhomogeneity within the sample [8].…”
Section: Introductionmentioning
confidence: 99%